War and Weapon Geochemistry: Key Areas, Applications and Impact on the Sustainable Development Goals (Al-Farooq Journal of Sciences, 2026)
This study aimed to clarify the key areas and applications of war and weapon geochemistry. War geochemistry examines the wide-ranging effects of war on Earth's chemical cycles, including metal and explosive contamination of air, soil and water. In order to comprehend post-conflict pollution, weapon geochemistry fundamentally bridges military technology and geochemical processes by concentrating on the materials found in weapons, their chemical composition, release mechanisms, and interactions with the environment. In short, weapon geochemistry is the study of the source materials (munitions, agents) that cause those impacts, while war geochemistry is the impact on the entire Earth system. In order to manage resources for present and future generations, sustainable development requires stable, peaceful conditions. War breaks this foundation, causing natural disasters that impede growth, making militarism itself a serious sustainability crisis. Clearly, war and weapon geochemistry can be regarded as subfields of environmental geochemistry.
Keywords: War Geochemistry, Weapon Geochemistry, Environmental Geochemistry